Evaluasi Proses Pengelolaan Inovasi dan Pengelolaan Penerimaan Perubahan dan Transisi Menggunakan Framework COBIT 5 pada Dinas Tenaga Kerja, Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Malang - Sarah Tsamara Dewanti; Buce Trias Hanggara; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Dinas Tenaga Kerja, Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DISNAKER-PMPTSP) Kota Malang is a government institution which facilitating programs and activities in labour sector as well as providing investment, licensing and non-licensing with one-stop integrated service system. Due to the lack of technological innovation which leads to the unprogressive service system development, DISNAKER-PMPTSP has several obstacles to tackle its service processes. Furthermore, when DISNAKER-PMPTSP Kota Malang is currently trying to revamp to the new information system, there is no proper management planning on the current transition between the old process to the new system. An evaluation is needed in managing innovation and managing change acceptance and transitioning by using the capabilities level assessment in the Manage Innovation (APO04) and Manage Change Acceptance and Transitioning (BAI07) processes using the framework Control Objective for Information and Related Technology (COBIT 5). The evaluation carried out by filling out the assessment documents in each process (APO04 and BAI07) gradually from level 0 to level 3 which is the level expected by DISNAKER-PMPTSP Kota Malang. Based on the results of the assessment, the capability level for the APO04 process was 66.67% and the BAI07 process was 73.08%, respectively at level 1. In conclusion, there is a gap between the APO04 and BAI07 processes, which are 2 levels. From the gaps that were found, several recommendations were made to meet the target level of each process.